DAMPAK KERUSAKAN EKOSISTEM MANGROVE TERHADAP KERAGAMAN JENIS HASIL TANGKAPAN NELAYAN DI WILAYAH PESISIR KECAMATAN PAGIMANA - Badjeber, Nikma; Salam, Aziz; Syamsuddin, Syamsuddin (JURNAL PERIKANAN TROPIS, 2020)
The purpose of the study was to determine the impact of mangrove ecosystem degradation to the diversity of the catch in the affected coastal area of Pagimana District. Surveys were done from July 2019 to February 2020 to collect data with questionnaires. Data is analyzed by quantitative descriptive analysis and NASA Arset analysis (GIS). Results of the study show that: (1) extensive damage to the mangrove tend to fluctuate from year to year; (2) the extent of damage is small to cause significant impact on fish catch; (3) diversity of the catch is still relatively high and the state of the waters is still relatively good.Keywords: Mangrove; ecosystem; degradation; catch; diversity.